Pregnancy complicated by cardiac disease: fetomaternal outcome - Singh, Ankita; Prasad, Sudha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Heart disease complicating pregnancy is an important indirect cause of maternal morbidity and mortality. The study aimed to know the prevalence of heart disease in pregnancy, type of lesions, maternal outcome (obstetric and cardiac) and fetal outcome. Methods: A retrospective study of 508 women with pregnancy complicated by cardiac disease who delivered at gestation age >28 weeks was carried out at Lok Nayak Hospital associated with Maulana Azad Medical College, New Delhi over a period of 2 years. Results: Among 508 patients, only 330 were booked cases and 92 were unbooked. 24 patients came to emergency first time with congestive heart failure. Rheumatic heart disease was the predominant lesion seen in 77.5% cases. Cardiac disease was diagnosed during index pregnancy in 43.5% cases. 12 cases underwent surgical intervention during pregnancy as they were refractory to medical management. Cesarean section was performed in 109 (21.4%) cases mainly for obstetric indication. Overall cardiac complication rate was 38.38%. Maternal mortality was seen in 6 cases. Small for gestation age was seen in 26.4% cases and preterm labor in 19.9 % cases. Conclusions: Patients in NYHA I /II have better fetomaternal outcome than in NYHA III/IV. Vaginal delivery is a safe option and caesarean section should be reserved mainly for obstetric indication. Multidisciplinary team approach can significantly improve maternal and fetal outcome.